Planning, Implementation and Experience of a Skill Development Workshop - Vámosi, Attila; Perge, Erika (International Journal of Engineering and Management Sciences, 2020)
The development of students’ different skills, both in primary and secondary schools, plays an extremely important role. The development of this age group in the form of playful activities can be effectively implemented. The article discusses the pedagogical background and planning steps of such occupations. A specific example of algorithmic skill development will be presented. We also list the experiences we have gained from holding this workshop, which may be helpful for the future development of the session.